2021
DOI: 10.3390/ma14061326
|View full text |Cite
|
Sign up to set email alerts
|

Warpage Optimisation on the Moulded Part with Straight Drilled and Conformal Cooling Channels Using Response Surface Methodology (RSM), Glowworm Swarm Optimisation (GSO) and Genetic Algorithm (GA) Optimisation Approaches

Abstract: It is quite challenging to control both quality and productivity of products produced using injection molding process. Although many previous researchers have used different types of optimisation approaches to obtain the best configuration of parameters setting to control the quality of the molded part, optimisation approaches in maximising the performance of cooling channels to enhance the process productivity by decreasing the mould cycle time remain lacking. In this study, optimisation approaches namely Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It was found that the thermal stability of addition-cured liquid silicone rubber was improved significantly. A conformal cooling channel (CCC) was employed in the plastic injection molding to enhance productivity and molded part quality [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the thermal stability of addition-cured liquid silicone rubber was improved significantly. A conformal cooling channel (CCC) was employed in the plastic injection molding to enhance productivity and molded part quality [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…They used Taguchi Design of Experiment (DOE) method and recommended an optimal setting for optimization of both shrinkage and cycle time together. Hanid et al [20] applied Moldflow and optimisation methods to report that CCCs can improve the component quality by reduction of the warpage.…”
Section: Introductionmentioning
confidence: 99%
“…The popularity of polymers is associated with relatively low prices, a very good price-quality ratio and general availability [ 3 ]. Requirements for their operating, strength and aesthetic properties are growing very dynamically [ 4 , 5 ], motivating more and more scientists and companies to search for new manufacturing technologies or their improvements [ 6 , 7 , 8 ]. Nowadays, despite many years of usage, still the most developing technology is injection molding [ 9 ].…”
Section: Introductionmentioning
confidence: 99%